2015
DOI: 10.1126/science.aab2012
|View full text |Cite
|
Sign up to set email alerts
|

Irrationality in mate choice revealed by túngara frogs

Abstract: Mate choice models derive from traditional microeconomic decision theory and assume that individuals maximize their Darwinian fitness by making economically rational decisions. Rational choices exhibit regularity, whereby the relative strength of preferences between options remains stable when additional options are presented. We tested female frogs with three simulated males who differed in relative call attractiveness and call rate. In binary choice tests, females' preferences favored stimulus caller B over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 27 publications
3
70
0
2
Order By: Relevance
“…The evaluation without a decoy results in f (A) = 0.4 and f (B) = 0.6. In the presence of the decoy, we predict that the choice probabilities can be evaluated as Another example can be taken from the studies of the frog mate choice [45], where frog males have attraction calls differing in either low-frequency sound or call rate. The males with lower frequency calls are denoted as A, while those with high call rate, as B.…”
Section: Quantitative Explanation Of Decoy Effectmentioning
confidence: 99%
“…The evaluation without a decoy results in f (A) = 0.4 and f (B) = 0.6. In the presence of the decoy, we predict that the choice probabilities can be evaluated as Another example can be taken from the studies of the frog mate choice [45], where frog males have attraction calls differing in either low-frequency sound or call rate. The males with lower frequency calls are denoted as A, while those with high call rate, as B.…”
Section: Quantitative Explanation Of Decoy Effectmentioning
confidence: 99%
“…Animals, including human beings, tend to respond more strongly to stimuli that are associated with the highest relative rewards (Staddon, 1975;Lea & Ryan, 2015). This selection strategy, with the general rule "the more, the better", has its roots in resource-scarce environments and is especially apparent when above-average alternatives exist.…”
Section: Flower-visiting Behaviourmentioning
confidence: 99%
“…This systemic violation of rationality has been studied extensively in the literature on psychology, marketing, consumer behavior and decision making, and replicated using many different experimental settings. The effect has been observed when subjects are given real incentives (Herne, 1998(Herne, , 1999Simonson and Tversky, 1992); when choice sets consist of non-market alternatives (Bateman et al, 2008), policy alternatives (Herne, 1997), gambles (Herne, 1999;Wedell, 1991) or investment alternatives (Schwarzkopf, 2003); when the experimental design is withinsubject (Lehmann and Pan, 1994;Simonson, 1989;Wedell and Pettibone, 1996) or betweensubject (Dhar and Glazer, 1996;Highhouse, 1996) and even when the subjects are hummingbirds (Bateson et al, 2003), gray jays (Shafir et al, 2002), túngara frogs (Lea and Ryan, 2015) or amoeboid organisms (Latty and Beekman, 2011). Furthermore, in a field experiment conducted in a grocery store, Doyle et al (1999) have shown that the asymmetric dominance effect plays an important role in actual markets.…”
Section: Introductionmentioning
confidence: 99%